Agent Oriented Requirement Engineering: A Case Study of Training the Trainer - Wai Shiang, Cheah; Chee Wyai, Loh; Yee Wai, Sim; bt Jali, Nurfauza (International Journal of Engineering and Technology, 2018)
Techniques such as interview and natural language elicitation are widely used for needs analysis, particularly in the modelling of software in Borneo. However, these approaches are often inadequate as they are subject to biases in interpretation by either the knowledge engineer or subject experts.Â Natural language specification tends to be overly flexible. It is also subjected to the perception and interpretation of the reader and writer. On the other hand, the interview process is always influenced by IT expertsâ€™ perception. Understanding requirements is an important study for ICT4D as most existing software has been targeted for a larger audience. This subjective approach is however, error-prone and could even lead to a failure of projects. We introduce an alternative approach to elicit the requirement of the rural community in Borneo through an agent-oriented models, AOM. AOM presents the requirements at a higher level of abstraction and supports social engagement across various stakeholders.Â We introduce process, models as well as a detail case study on training the trainer programme (ICT for transformation) in Bario, Sarawak. The models have provided insights into community needs and thus facilitating the design of IT training program that addresses their concerns.Â Â